Taxation and On-The-Job Training Decisions - Rosen, Harvey S. (The Review of Economics and Statistics, 1982)
This paper is an econometric analysis of the on-the-job training (OJT) decisions of a group of white American males during 1975. The data are obtained from the Panel Study of Income Dynamics, which asked a very careful series of questions concerning the individual's OJT status. Each individual's internal rate of return is estimated and used as an explanatory variable to predict the probability of taking OJT. The individual's marginal tax rate is also entered in the equation. The results suggest that income taxation has tended to increase the probability of being involved in OJT. I conjecture that this is because income taxation makes investment in physical capital a less desirable vehicle for carrying consumption into the future, and hence increases the attractiveness of human capital.